Resistência ao escorregamento de revestimentos cerâmicos: avaliação por diferentes métodos, correlações com a topografia e o desgaste da superfície durante o uso - Lot, Ana Virgínia (2020)
The development of ceramic floors for safe use in environments associated with slip and fall accident risks, which are even higher in the presence of water and contaminants, deals with the following difficulties: 1) although some roughness increase may contribute to the slip resistance of the surfaces, on the other hand, this can make them more susceptible to grime and wear. 2) there is a wide variety of methods for evaluating and classifying tiles as recommended or not for use in slip-risk areas and results of different methods may disagree between them. 3) satisfactory slip performances of floors measured before installation may not be maintained during their use. In this sense, the objective of this work was to contribute to the development of safe and durable ceramic floors by identifying the characteristics of the surfaces related to their performance and investigating how they vary over time. Several types of commercial floors were characterized regarding their slip resistance - with the DS, BOT-3000 and Pendulum devices - and staining resistance. The results were correlated with roughness parameters obtained by profilometers for the identification of the surface’s characteristics relevant to their performance. The samples were subjected to heavy traffic, to accelerate their wear and grime, and re-evaluated. Surface changes were observed, such as reductions in average roughness and profile amplitude and inclination, as well as the increase in the spacing between irregularities and rounding of their shapes. Consequently, all the high initial slip resistance surfaces presented a deterioration of this property in the three methods of evaluation. Surface aspects were also associated with tendency to grime and a new complementary analysis to the usual laboratorial method for predicting ceramic floors cleanability was proposed.